2015
DOI: 10.4103/2152-7806.159383
|View full text |Cite
|
Sign up to set email alerts
|

Preventing proximal junctional failure in long segmental instrumented cases of adult degenerative scoliosis using a multilevel stabilization screw technique

Abstract: Background:The authors sought to demonstrate the safety and effectiveness of the multilevel stabilization screw (MLSS) technique in decreasing the incidence of proximal junctional failure in long segmental instrumented fusions for adult degenerative scoliosis.Methods:Institutional review board approval was obtained and all patients with adult spinal deformity who underwent the MLSS technique were analyzed. A neuro-radiologist and spine-focused neurosurgeon not involved with the surgical treatment performed rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…They reported that transvertebral screw fixation had good fixation force similar to the traditional PS fixation, and it can be a viable therapeutic option for fixation in a salvage procedure, if PS insertion is not possible 17) . Sandquist et al reported on the multilevel stabilization screw technique for decreasing the incidence of proximal junctional failure in long segmental instrumented fusions for adult degenerative scoliosis 18) . These reports suggested that transvertebral screws are a useful device to obtain favorable surgical outcomes.…”
Section: The Deps Technique Is a Modification Of The Pes Technique Reported By Matsukawa Et Al The Pesmentioning
confidence: 99%
“…They reported that transvertebral screw fixation had good fixation force similar to the traditional PS fixation, and it can be a viable therapeutic option for fixation in a salvage procedure, if PS insertion is not possible 17) . Sandquist et al reported on the multilevel stabilization screw technique for decreasing the incidence of proximal junctional failure in long segmental instrumented fusions for adult degenerative scoliosis 18) . These reports suggested that transvertebral screws are a useful device to obtain favorable surgical outcomes.…”
Section: The Deps Technique Is a Modification Of The Pes Technique Reported By Matsukawa Et Al The Pesmentioning
confidence: 99%
“…For each study, PJK incidence, Revision Rate for PJK (RR), PJF incidence, reported clinical outcomes and complications were reported in Table 3. Twelve of the included studies reported on PJK incidence, 28-31,33-36,38,39,41,43 10 on revision rate for PJK, 28-31,33,35,36,38,39,41 13 on PJF incidence, 29,32,34-40,42-45 5 on any clinical outcome measure 28,38,40,41,45 and 10 on complications. 28-30,35-39,41,45 Four studies 28-30,37,45 did not elaborate on the type of complications, and could thus not be converted to the classification of Glassman et al 27 If reported, the clinical outcome measures were further elucidated in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, 4 were prospective- and 14 were retrospective cohort studies. The studies that were included reported on tether fixation, 28 - 34 prophylactic 2-level vertebroplasty (2-PVP), 32 , 35 - 40 transverse process hooks (TPH), 32 , 41 , 42 flexible rods (FR), 43 multilevel stabilization screw (MLSS), 44 and sublaminar tapes (ST). 45 These surgical techniques are schematically illustrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations